Heritage on the Margins? Central and Eastern European Perspectives - Ledinek Lozej, Špela; Rogelja Caf, Nataša (Traditiones, 2025)
This introductory article reflects heritage-making processes in the Central and Eastern European (CEE) context. It links discussions of the ZRC SAZU multidisciplinary research program on heritage with case studies presented at the conference Heritage on the Margins? (November 2023, Ljubljana). The focus of the article is heritage formation and the performative influence of heritage in minority, remote, linguistic, industrial, (post)imperial, (post)socialist and otherwise marginalized settings.